Increased expression of thyroid hormone receptor alpha and estrogen receptor alpha in breast cancer associated with thyroid cancer. Issue 6 (June 2021) - Kim, Ye An; Kim, Young A.; Cho, Sun Wook; Song, Young Shin; Min, Hye Sook; Park, In Ae; Park, Do Joon; Hwang, Ki-Tae; Park, Young Joo
Abstract: Introduction: Breast cancer co-occurred with thyroid cancer might be associated with thyroid hormone receptor (TR) and estrogen receptor (ER), but few have been reported. We aimed to investigate the expression and prognostic significance of ERs and TRs in such settings. Material and methods: Tissue microarrays were constructed from 75 patients with breast and thyroid cancer (BC + TC) who were retrospectively recruited between 1999 and 2012 and 147 with breast cancer only (BC controls). The ERα, ERβ, TRα, and TRβ expression levels were analyzed by immunohistochemistry. Results: TRα expression was more frequently observed in the BC + TC group than the BC control group both in the normal (51.5% vs 23.3%, respectively, p  = 0.009) and cancer tissues (21.6% vs 6.8%, respectively, p  = 0.001). The BC + TC group showed greater ERα-positivity in the cancer tissues (79.7% vs 58.7%, respectively, p  = 0.002) than the BC control group. The degree of ERα- and TRα-positivity was unchanged by radioactive treatment or serum thyroid stimulating hormone levels. In the BC + TC group, ERα-positivity was associated with earlier disease stage I/IIA (81.0% vs 50.0%; p  = 0.031) and lower recurrence rates (8.5% vs 40.0%; p  = 0.002). TRα-positivity alone was not associated with any recurrence-free survival-related differences, and ERα- and TRα-negativity were associated with significantly shorter recurrence-free survival (p < 0.001). Conclusion: Enhanced ERα and TRα expression in breast cancer is associated with thyroid cancer occurrence, and the observed association with prognosis suggests the possible role of ERs and TRs in the link between breast cancer and thyroid cancer. Highlights: - ERα and TRα expression was stronger in BC patients with TC co-occurrence. - Recurrence-free survival was also associated with ERα and TRα. - First study to investigate TR and ER expression in BC after TC occurrence. - ERα and TRα-positivity may have prognostic value in concomitant BC and TC.